Determinants of CO2 emissions in Brazil and Russia between 1992 and 2011: A decomposition analysis - Rustemoglu, Hasan; Rodriguez Andres, Antonio (Elsevier Sci Ltd, 2016)
This paper deals with the decomposition analysis of energy-related CO2 emissions in Brazil and Russia from 1992 to 2011. The refined Laspeyres index (RLI) method applied and both aggregated and sectoral changes in CO2 emissions decomposed. Brazil's and Russia's economies divided into three economic sectors including agriculture, industry and services. Impact of four main factors, such as economic activity, employment, energy intensity, and carbon intensity in CO2 emissions changes were analyzed. The aggregated decomposition analysis revealed that Brazil is still far from a decoupling between economic growth and carbon dioxide emissions where Russia achieved a substantial decline in carbon emissions mainly due to the improved energy intensity. The empirical findings of sectoral decomposition analysis emphasized that the economic activity was the major CO2 increasing factor in Brazil's economic sectors. On the other hand the economic activity effect followed a reducing impact in Russia's sectoral emissions until 2000. The structural changes between sectors and their impacts on CO2 emissions were captured by employment effect. Energy intensity and carbon intensity effects underlined that environmental sustainability widely neglected in Brazil and Russia during the study period. The results yield important hints for energy planning and sustainable environment. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CO2 emissions; Environmental sustainability; Decomposition analysis; Refined Laspeyres index method; Brazil; Russia